CATACOMB WITH A BELT PACK OF «PUN-TURKISH TYPE» FROM THE GOUST BURIAL (BY MATERIALS FROM V.I. DOLBEZHEV’S EXCAVATIONS OF 1890) - S. A. GONCHAROV; A. A. KADIEVA (Кавказология)
The article presents an analysis of the results of the archaeological excavations of the medieval burial ground situated near the Goust village in Ingushetia. It was first found by V.I. Dolbezhev in 1890. The characteristic funeral equipment of Saltovo-Mayatskaya culture time the second part of the 8-9 A.D. was discovered there: overlays on the belt with a Lotus-shaped ornament, glass ring type «Orbeti» and bells of bronze. Besides, we paid attention to the chronology of the belts of «pun-turkish type» in the North Caucasus. That type appeared on the Altai in the 7 A.D. Our research shows that this type of belts was in use on the North Caucasian territories from the second part of the 8 to the 11 A.D.